Information Security Governance - Solms, S.H. (Springer US, 2009)
IT Security governance is becoming an increasingly important issue for all levels of a company. IT systems are continuously exposed to a wide range of threats, which can result in huge risks that threaten to compromise the confidentiality, integrity, and availability of information. This book will be of use to those studying information security, as well as those in industry. Key Features: The book provides a point of entry into the subject with an easy-to-understand model of Information Security Governance Book addresses information security from the governance side, with special emphasis on the accountability of top management Ideal for the professional market as it discusses some international best practices for IT Security Governance in detail